Penpulimab, an Fc-Engineered IgG1 Anti-PD-1 Antibody, With Improved Efficacy and Low Incidence of Immune-Related Adverse Events - Huang, Zhaoliang; Pang, Xinghua; Zhong, Tingting; Qu, Tailong; Chen, Na; Ma, Shun; He, Xinrong; Xia, Dennis; Wang, Max; Xia, Michelle; Li, Baiyong (Frontiers in Immunology, 2022)
Background: IgG4 anbibodies are deficient in stability and may contribute to tumor-associated escape from immune surveillance. We developed an IgG1 backbone anti-programmed cell death protein-1 (PD-1) antibody, penpulimab, which is designed to remove crystallizable fragment (Fc) gamma receptor (FcγR) binding that mediates antibody-dependent cell-mediated cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP) and proinflammatory cytokine release. Methods: Aggregation of different anti-PD-1 antibodies was tested by size exclusion chromatography, and melting temperature midpoint (Tm) and aggregation temperature onset (Tagg) were also determined. The affinity constants of penpulimab for PD-1 and human FcγRs were measured by surface plasmon resonance and biolayer interferometry. ADCC and ADCP were determined in cellular assays and antibody-dependent cytokine release (ADCR) from human macrophages was detected by ELISA. Binding kinetics of penpulimab to human PD-1 was determined by Biacore, and epitope/paratope mapping of PD-1/penpulimab was investigated using x-ray crystallography. Additionally, patients from six ongoing trials were included for analysis of immune-related adverse events (irAEs). Results: Penpulimab demonstrated better stability and a lower level of host-cell protein residue compared with IgG4 backbone anti-PD-1 antibodies. As expected, penpulimab exhibited no apparent binding to FcγRIa, FcγRIIa_H131, FcγRIIIa_V158 and FcγRIIIa_F158, elicited no apparent ADCC and ADCP activities, and induced no remarkable IL-6 and IL-8 release by activated macrophages in vitro. Penpulimab was shown in the co-crystal study to bind to human PD-1 N-glycosylation site at N58 and had a slower off-rate from PD-1 versus nivolumab or pembrolizumab. Four hundred sixty-five patients were analyzed for irAEs. Fifteen (3.2%) patients had grade 3 or above irAEs. No death from irAEs was reported. Conclusions: IgG1 backbone anti-PD1 antibody penpulimab has a good stability and reduced host cell protein residue, as well as potent binding to the antigen. Fc engineering has eliminated Fc-mediated effector functions of penpulimab including ADCC, ADCP and reduced ADCR, which may contribute to its more favorable safety profile.